Genome Sequence of the Salmonella enterica subsp. enterica Serovar Namur Strain 05-2929, Lacking the Salmonella Atypical Fimbrial Operon. - Barbau-Piednoir, Elodie; Sophie Bertrand; Nancy Roosens; Sigrid C.J. De Keersmaecker (Genome Announc, 2014)
This paper announces the genome sequence and annotation of Salmonella enterica subsp. enterica serovar Namur strain 05-2929. S. Namur is a new serovar (39:z4,z23:-) that was isolated from a patient with salmonellosis in 2005 in Namur, Belgium, and has been identified as lacking the Salmonella atypical fimbrial (saf) operon.